2012
DOI: 10.4103/0970-9290.104951
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of AH Plus, EndoREZ and Epiphany against microorganisms

Abstract: It could be concluded that AH Plus and EndoREZ showed antimicrobial activity against all the tested microorganisms. No antimicrobial activity was observed for Epiphany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…These results are in accordance with other studies where fresh AH Plus and iRoot SP had antibacterial action against E. faecalis by time kill assay [ 15 ], ADT, DCT, and modified DCT [ 1 , 2 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with other studies where fresh AH Plus and iRoot SP had antibacterial action against E. faecalis by time kill assay [ 15 ], ADT, DCT, and modified DCT [ 1 , 2 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…El sellador resinoso AH Plus posee una composición similar al sellador a base de resina epóxica Topseal, cemento endodóntico utilizado en esta investigación (11). Maekawa et al, en el 2012, utilizaron el método de difusión en agar Müller-Hinton para comprobar la actividad antimicrobiana de selladores endodónticos frente al Enterococcus faecalis y otras especies bacterianas comunes en las infecciones del sistema del conductos radiculares (12). La media del halo inhibitorio del sellador resinoso AH Plus fue de 7,92 mm que guarda similitud con el halo inhibitorio provocado por Topseal, utilizado en esta investigación.…”
Section: Efi Cacia Antibacteriana De Tres Selladores Endodónticos Freunclassified
“…20 The reports of few studies state that EndoREZ also showed greater inhibition zones. 15,21 Ustun et al 22 and Zhang et al 23 showed that EndoREZ was still bacteriostatic on the 7th day.…”
Section: Ijpcdrmentioning
confidence: 99%
“…6,8 It adapts closely to the canal walls with minimal shrinkage after setting, and has long-term dimensional stability and better sealing properties due to good flow. 19,21,22 The reason for the high antibacterial activity of this sealer could be due to the unpolymerized residues during polymerization, in addition to the amine and epoxy resin components of the sealer. 19 The oxygen inhibition layer of the surface of any polymerizing resin leaves an uncured monomer layer, which could be another reason.…”
Section: Ijpcdrmentioning
confidence: 99%
See 1 more Smart Citation